2013
DOI: 10.33225/jbse/13.12.682
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Storylines Embedded Within Context-Based Learning Approach on Grade 6 Students’ Understanding of ‘Physical and Chemical Change’ Concepts

Abstract: Alternative conceptions of ‘physical and chemical change’ concepts to minimize their effects on further learning should be handled at lower secondary school in that these concepts are formally introduced at grade 6. This study aimed to investigate the effect of storylines embedded within context-based learning approach on grade 6 students’ understanding of ‘physical and chemical change’ concepts. To probe the students’ conceptions, Chemical and Physical Change Concept Questionnaire (CPCCQ) was employed as pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Hence, the MANOVA result shows that the mean achievement gain is higher in group B (CBL) and group C (PBL) than in group A. This result is in line with Demircioğlu et al [44] who found that the CBL strategy aids active learning which helps students achieve higher levels of engagement and mastery of higher‐order programming abilities thus allowing the lecturers to maintain students' attentiveness and deep learning, which may explain why the treatment group outperformed the control group.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, the MANOVA result shows that the mean achievement gain is higher in group B (CBL) and group C (PBL) than in group A. This result is in line with Demircioğlu et al [44] who found that the CBL strategy aids active learning which helps students achieve higher levels of engagement and mastery of higher‐order programming abilities thus allowing the lecturers to maintain students' attentiveness and deep learning, which may explain why the treatment group outperformed the control group.…”
Section: Discussionsupporting
confidence: 89%
“…The abstract nature of understanding elemental properties has led to innovation in the adoption of parallel metaphors not dissimilar to the mnemonic approach for concepts but allowing students to relate to chemical properties through stories or personalization of the rules. For example, instructors adopt a storyline approach to teaching 11 to 12 year old children the elements’ essential properties, which allows them to develop mental images for concepts of chemical change, bonding, and electrons . In this method, scientific theories replace a portion of the students’ misconceptions, although some students develop new misconceptions, and others are resistant to change.…”
Section: Teaching the Periodic Table Of The Elementsmentioning
confidence: 99%
“…For example, instructors adopt a storyline approach to teaching 11 to 12 year old children the elements' essential properties, which allows them to develop mental images for concepts of chemical change, bonding, and electrons. 16 In this method, scientific theories replace a portion of the students' misconceptions, although some students develop new misconceptions, and others are resistant to change.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Instead, many researchers recommend using narrative, given its open-ended and flexible nature (Avraamidou & Osborne, 2009 ; Millar & Osborne, 1998 ; Norris et al, 2005 ; Torrance & Galbraith, 1999 ). On the one hand, this storytelling approach is found to be effective for students’ science conceptualization (e.g., students’ understanding of physical and chemical change, Demircioğlu et al, 2013 ). What is more, narrative has been considered as more compatible with a constructivist approach because it can be used to connect to learners’ personal experiences and promote deep meaning-making activities (Anilan, 2018 ; Levinson, 2008 ; McKee & Ogle, 2005 ; Mott et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%